Fulfilling the Rehabilitation Rights of Child Prisoners in Drug Cases: A Review of the Implementation of the Child Protection Law in Tanjungbalai City - Zuliah, Azmiati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to describe the fulfillment of the Rehabilitation Rights of Child Prisoners in the Tanjungbalai City Narcotics Case according to the Child Protection Law. Law Number 35 of 2014 concerning Child Protection (UU PA) is the legal basis that regulates the rights and protection of children in Indonesia. The research method used in the research is empirical juridical. In imposing sanctions on children who commit criminal acts of narcotics abuse, they are often sentenced to imprisonment, this does not solve children's problems. In fact it is prone to violations against children, whereas in Law Number 11 of 2012 concerning the Children's Criminal Justice System, it is mandatory to prioritize restorative justice. Arrest, detention or criminal imprisonment of children is only carried out in accordance with applicable law and can only be done as a last resort. The results of the research show that the overall indicators of success in developing correctional students at Tanjungbalai Detention Center are: 1) Students carry out worship according to their respective religions, both individually and in congregation; 2) Students can study formally at Tanjungbalai Detention Center; 3) Students behave, behave and are aware of the law, nation and state; 4) Students have skills as a provision when they have finished serving their sentences.